2003
DOI: 10.1128/jvi.77.8.4722-4730.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Foamy Virus Envelope Glycoprotein-Mediated Entry Involves a pH-Dependent Fusion Process

Abstract: In general, enveloped viruses use two different entry strategies and are classified accordingly into pHdependent and pH-independent viruses. Different members of the retrovirus family use one or the other strategy. Little is known about the uptake of foamy viruses (FV), a special group of retroviruses, into the target cells. In this study, we examined the pH dependence of FV entry by analyzing FV envelope glycoprotein (Env)-mediated infection of target cells with murine leukemia virus or FV vector pseudotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 37 publications
8
50
0
Order By: Relevance
“…The function of the FP is still unclear. But it has been proven that the FPs in almost all FVs need to be exposed to a low pH, in order to insert themselves into the target membranes (Picard-Maureau et al, 2003).…”
Section: Conserved Motifs In Envelope Glycoproteins Of Fvsmentioning
confidence: 99%
“…The function of the FP is still unclear. But it has been proven that the FPs in almost all FVs need to be exposed to a low pH, in order to insert themselves into the target membranes (Picard-Maureau et al, 2003).…”
Section: Conserved Motifs In Envelope Glycoproteins Of Fvsmentioning
confidence: 99%
“…However, while the results with various lysomotropic reagents, such as concanamycin A, ammonium chloride, methylamine, and baWlomycin A1, were consistently pointing to a pH-dependent cellular uptake, the results obtained with chloroquine diverged and also indicated that there are as yet not understood diVerences to other glycoproteins that show pH dependency of their fusion activity [97].…”
Section: Envmentioning
confidence: 93%
“…Concerning the cellular uptake of FV virions, it was established that it likely follows a pathway known from some other enveloped viruses such as inXuenza virus or VSV [97] that is virus uptake relies on the acidiWcation of Env for the generation of a fusion-competent molecule [97]. However, while the results with various lysomotropic reagents, such as concanamycin A, ammonium chloride, methylamine, and baWlomycin A1, were consistently pointing to a pH-dependent cellular uptake, the results obtained with chloroquine diverged and also indicated that there are as yet not understood diVerences to other glycoproteins that show pH dependency of their fusion activity [97].…”
Section: Envmentioning
confidence: 99%
“…33,35 Retroviral entry mediated by receptor priming and low-pH triggering of the envelope glycoprotein has, however, been reported in the case of the avian leucosis virus and the foamy virus. 50,51 To verify whether the envRBV-3 mediated fusion process can occur under acidic conditions, envRBV-3 expressing cells have been induced to undergo syncytium formation upon the artificial lowering of the extracellular pH. We have shown that envRBV-3 is able to induce membrane fusion both at neutral and low pH, with an optimal pH around 5.0.…”
Section: Hiv Rbv-3 Escapes Spla 2 Blockade By Using Endosomal Trafficmentioning
confidence: 97%
“…The pH dependence of the fusion activity of envRBV-3 protein was analysed by using a cell-to-cell fusion assay as described 51 with minor modifications. The 293 cells (4x10 5 ) were transiently transfected with 2 μg of pEnvRBV-3, pAD-2 or pCMV-G and 2 μg of the Tat expression vector pCMVTat.…”
Section: Env-mediated Membrane Fusion Assaymentioning
confidence: 99%